Online Tools in the Function of Internal Communication in the Media - Ljajic, Samir; Dojcinovic, Nikola (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
The functioning of modern society in the 21st century is conditioned by the use of computerized technology in almost all areas. The modern age is characterized by digital networking of contacts through online tools that are based on the platform of the global network, the Internet. The online tools make it possible to establish communication without space-time limitations, which can be of great importance in emergency circumstances in order to achieve internal (business) communication. The success of media organizations can largely depend on the way internal communication is organized. The possibility of establishing internal communication among media workers at any time and in any place is especially important. The basic idea in this paper is to examine whether media workers used online tools for the purpose of internal communication during the state of emergency (caused by the COVID-19), in order to perform work in aggravating, emergency circumstances. The potentials of online tools for internal communication were examined, as well as the attitudes of media workers regarding the implementation of internal communication through online tools, and their attitudes regarding the importance of internal communication for business efficiency. Sixty-three media workers (from seven media organizations) were surveyed using a questionnaire based on a Likert-type scale. The age of the surveyed workers varied from 20 to 55 years. The theoretical part of the paper includes the definition of online tools and concepts related to the research topics, as well as a chapter dedicated to the importance of internal communication. The results of the research were then presented and conclusions were drawn.